2002
DOI: 10.1002/1521-3773(20020802)41:15<2832::aid-anie2832>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

C2-Symmetric Chiral Pentacyclic Guanidine: A Phase-Transfer Catalyst for the Asymmetric Alkylation of tert-Butyl Glycinate Schiff Base

Abstract: The enantioselective alkylation of the Schiff base 2 was carried out in the presence of a novel phase‐transfer catalyst, the guanidine‐containing pentacyclic compound 1. The product 3 was obtained with enantiomeric excesses of 76–90 % (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…[24][25][26][27] or other designed catalysts (for representative examples, see refs. [28][29][30][31][32], only a few synthetic applications for complex natural products have been reported (23). Recently, we developed two-center catalysts that promote phase-transfer alkylations and Michael reactions with high substrate generality (14).…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] or other designed catalysts (for representative examples, see refs. [28][29][30][31][32], only a few synthetic applications for complex natural products have been reported (23). Recently, we developed two-center catalysts that promote phase-transfer alkylations and Michael reactions with high substrate generality (14).…”
Section: Resultsmentioning
confidence: 99%
“…Our results and the selectivities observed are in agreement with the reactions reported by Nagasawa using structurally similar pentacyclic guanidine catalysts. 8 We next focused on the application of 7a to the PTC epoxidation of chalcones 10a-e 9 (Scheme 3) and found it to be an excellent catalyst for this transformation. We initially investigated the epoxidation of chalcone 10a (R 1 = R 2 = Ph) with NaOCl and found that the catalyst was effective over a range of 0.1 to 0.025 equivalents and gave the chalcone epoxide 11a in consistent ee and in high yields ( Table 2, entries 1-3).…”
Section: Phase Transfer Alkylation and Epoxidation Reactionsmentioning
confidence: 99%
“…8) Nagasawa and co-workers reported chiral guanidinium salts as a new type of PTC that promoted O'Donnell's alkylation under PTC conditions. 9) In this communication, we report the catalytic asymmetric Michael reaction of a glycine Schiff base using bis-ammonium salts as PTCs. [10][11][12][13][14][15][16] Binaphthol and its derivatives are known to be a versatile starting compound for the preparation of chiral catalyst.…”
mentioning
confidence: 99%